Transnational Mobilities as a Way of Life Among Older Migrants from Southern Europe. Issue 5 (8th February 2016) - Bolzman, Claudio; Kaeser, Laure; Christe, Etienne
ABSTRACT: This paper focuses on older Spanish, Italian, and Portuguese migrants who spent their working lives in Switzerland and explores their different forms of geographical mobility between Switzerland and their home countries. Although drawing inspiration from the transnationalism literature and the new mobilities paradigm, we do not neglect a more structural perspective that stresses the constraints endured by older migrants when they try to build mobile lives. We approach the issue of transnational mobility using mainly quantitative data from the survey Vivre–Leben–Vivere, which focuses on the living conditions and health of individuals aged 65 years and above currently living in Switzerland. Within this survey, an oversample of approximately 300 older immigrants of Italian, Spanish, and Portuguese origin aged between 65 and 79 years was conducted in Geneva and Basel. The quantitative data are complemented by material from interviews with three Spanish families living in Geneva. Our data show that to 'settle in Switzerland' or to return home does not imply that older immigrants' transnational mobility ceases. To some extent, it could be argued that they never really 'settled' and transnational mobility is a way of life that is more adapted to the duality of resources and references that they have built up during their adult life. Their geographical mobility can take different forms and is adapted to legal constraints, to family configurations, and to individual situations. Copyright © 2016 John Wiley & Sons, Ltd.